Penyelesaian Konflik Sertifikat Hak Milik yang Tumpang Tindih melalui Mediasi - Angga Alfian; Angga Bela Dinata; Mega Trio Kristian Ade Putra; Udea Triyunita (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
This research aims to explore the potential for using mediation in resolving conflicts over overlapping property rights certificates. The research method used is empirical legal research with primary and secondary data. Primary data was obtained from cases of property rights certificate conflicts that were successfully resolved through mediation, while secondary data came from literature research for theoretical analysis. Qualitative analysis was conducted on the data with a focus on emerging patterns, themes and findings. The research results show that the factors causing conflict involve administrative errors, changes in property boundaries, failure to verify ownership, changes in the legal status of property, and territorial division. Mediation through the National Land Agency (BPN) is an effective alternative in resolving this conflict. The agreement resulting from the mediation is recorded in the Minutes of Mediation Holding and Dispute Settlement Agreement Letter, providing a legal basis for follow-up registration of land rights to BPN. In conclusion, mediation can be an effective tool for resolving overlapping property rights certificate conflicts, providing a quick, cost-effective solution and considering the interests of all parties.